Molecular characterization of Mycobacterium bovis strains isolated from cattle and humans by spoligotyping and 24-locus MIRU-VNTR, and prevalence of positive IGRA in slaughterhouse workers in Southern Turkey. - Guuml;ven Gouml;kmen, T.; Yakici, G.; Kalayci, Y.; Turut, N.; Meral Ocal, M.; Haliguuml;r, M.; Guuml;naydin, E.; Kouml;ksal, F. (School of Veterinary Medicine, University of Shiraz, 2022)
Mycobacterium bovis is a zoonotic member of the Mycobacterium tuberculosis complex with a wide range of hosts, mainly cattle. Molecular epidemiological studies should be conducted to determine the transmission route, zoonotic risk factors, and phylogenetic relationships of M. bovis strains. Aims: This study aimed to characterize bovine and human M. bovis isolates by molecular methods.Molecular characterization and clonal relationship of strains isolated from tissue and organ samples of 76 cattle with positive tuberculin tests were collected from a slaughterhouse, and four M. bovis strains isolated from clinical materials of patients with suspected pulmonary TB isolates were analyzed using 24-locus MIRU-VNTR and spoligotyping methods. QuantiFERON-TB Gold Plus (QFT-Plus; Qiagen) was used to determine the prevalence of latent TB infection among 21 slaughterhouse personnel including 7 veterinarians, 12 butchers, 1 caretaker, and 1 veterinary technician.SB0288/SIT685 type was detected in both cattle and humans by the spoligotyping method. When evaluating MIRU-VNTR, the presence of a 100% compatible pattern between human and bovine isolates was not detected, but some human samples were found to be 91.6% similar to a bovine sample. In addition, 21 slaughterhouse workers were screened with the interferon gamma-released assay (IGRA) and a 23.8% positivity was detected.Clonal similarity was determined between the bovine and human isolates using the MIRU-VNTR and spoligotyping methods and IGRA positivity in the occupational group suggested that M. bovis might be associated with pulmonary tuberculosis in humans.
Keywords: Original Article; 3. Good health